Genetic Analysis of Yellow Rust Resistance in Wheat - (:unkn) unknown (My University, 2020)
Wheat production is affected by several biotic and abiotic stresses and fungal pathogens are the most important disease factor. Globally important fungal yellow rust diseases of wheat caused by obligate parasite biotrophic fungus named “Puccinia striiformis f. sp. tritici” is causing loss of quality in a grain and yield at significant level in worldwide. The obligate parasites are highly specialized, and significant variation exists in the pathogen population for virulence to specific resistance genes. Growing cultivars resistant to rust is the most sustainable, cost-effective and environmentally friendly approach preferred to use chemical pesticides for controlling yellow rust diseases. For this reason, determination and evaluation of the presence of wheat varieties resistant and susceptible to yellow rust diseases is of great importance for breeding. Genetic diversity and durability are the two most important features of the resistance for the global wheat improvement programs. Genetic analysis to understand the genetic basis of resistance is important to control of wheat yellow rust. In addition to traditional characterization of resistance using physiological methods, wheat populations also have been genetically characterized using DNA-based molecular markers related with genes to identify and select the presence or absence of genes in early generation populations that could contribute to durable resistance. This review will discuss about yellow rust disease resistance in wheat genotypes in the frame of molecular breeding efforts in combination with our previous findings and current technological developments at molecular level. This information will serve as a foundation for plant breeders and geneticists to develop durable yellow rust-resistant wheat varieties through marker-assisted breeding or gene pyramiding.